Early Adoption of Technically Complex Robotic Ventral Hernia Repair in a Low-Volume Center: A Retrospective Comparative Analysis with Consecutive Open Cases - Andraž Hubad; Aleš Tomažič; Blaž Trotovšek; Primož Sever; Jan Grosek (Journal of Clinical Medicine, 2026)
Background/Objectives: Robotic-assisted abdominal wall reconstruction is increasingly used for ventral hernias; however, implementation in low-volume settings and early adoption of technically complex cases remain controversial. This study aimed to evaluate perioperative outcomes of robotic ventral hernia repair with early inclusion of technically complex cases and to compare these results with open surgery. Methods: Prospectively collected data were retrospectively analyzed for consecutive technically complex robotic ventral hernia repairs performed between September 2021 and December 2025. A cohort of consecutive open Rives–Stoppa repairs was included for comparison (n = 21 per group). Outcomes included operative time, length of hospital stay (LOS), and perioperative complications. Results: Operative time was significantly longer in the robotic group (median 310 vs. 118 min, p < 0.001). The median LOS was significantly shorter following robotic repair (3 vs. 5 days, p = 0.0018). Postoperative complications occurred in 10% of robotic cases and 24% of open cases (p = 0.41). Major complications and reoperation rates were low and comparable between groups. Technically complex robotic cases, including procedures requiring component separation, were introduced early and were associated with acceptable short-term outcomes. Conclusions: Technically complex robotic hernia repair was associated with significantly shorter hospital stay compared with open surgery, despite longer operative times and higher procedural complexity. Complication rates were comparable between groups. Early inclusion of technically complex cases was not associated with a statistically significant increase in short-term complications.